2019
DOI: 10.3324/haematol.2018.214809
|View full text |Cite
|
Sign up to set email alerts
|

MR4 sustained for 12 months is associated with stable deep molecular responses in chronic myeloid leukemia

Abstract: The majority of patients with newly diagnosed chronic myeloid leukemia (CML) will enjoy a life expectancy equivalent to that of unaffected individuals, but will remain on life-long treatment with a concomitant requirement for on-going hospital interactions for molecular monitoring and drug dispensing. In order to determine more accurately the frequency of monitoring required, we performed a ‘real-life’ retrospective single-center cohort study of 450 patients with CML in at least major molecular remission (MR3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Importantly, failure to sustain a MR4 was the only significant variable for loss of MMR in multivariate analysis. 59 We also found that sustained undetectable BCR-ABL1 (MR4.5) was associated with sustained MMR. 21 Conversely, MMR was lost in six of 22 (27%) patients with sustained detectable BCR-ABL1 and was associated with the acquisition of imatinib-resistant BCR-ABL1 kinase domain mutations in three of six patients.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Importantly, failure to sustain a MR4 was the only significant variable for loss of MMR in multivariate analysis. 59 We also found that sustained undetectable BCR-ABL1 (MR4.5) was associated with sustained MMR. 21 Conversely, MMR was lost in six of 22 (27%) patients with sustained detectable BCR-ABL1 and was associated with the acquisition of imatinib-resistant BCR-ABL1 kinase domain mutations in three of six patients.…”
Section: Introductionmentioning
confidence: 60%
“…A recent single-center review of 450 patients demonstrated that sustained MR4 for at least 12 months represented a secure response threshold. 59 This finding only applied to compliant patients with no history of previous TKI resistance who received standard-dose TKI. No such patient lost a MMR, whereas loss of MMR occurred in 25% of patients who had not achieved a MR4.…”
Section: Introductionmentioning
confidence: 99%
“…19 D'Adda et al reported that patients with the e13a2 transcript were less likely to achieve major molecular response (MMR; <0.1% IS) and hence had less chance of enrolling into trials of treatment discontinuation. 20 Furthermore, we and others reported in small patient cohorts that patients with the e13a2 transcript were more likely to experience an increase in BCR-ABL1 transcripts after treatment discontinuation and had lower rates of treatment-free remission 21,22 The differences in these outcome measurements between patients with e13a2 and e14a2 transcript types could be due to biological differences in the activity of the respective oncoproteins, or could alternatively, at least in part, be the result of technical factors, such as differential sensitivity of the BCR-ABL1 detection assay currently in use, to the two isotypes.…”
mentioning
confidence: 75%
“…The stability of the molecular response has already been proposed as a variable influencing TFR success [ 17 ], but not enough data are currently available to establish a definite link. Although the stability of MR 4.5 is known to be associated with improved patient outcomes [ 34 , 35 ], to our knowledge, this is the first time it has been reported as a potential predictor of TFR success. However, it should be noted that the number of patients in some of the groups was very small.…”
Section: Discussionmentioning
confidence: 99%